2010
DOI: 10.1016/j.crci.2010.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembling polysaccharide systems based on cyclodextrin complexation: Synthesis, properties and potential applications in the biomaterials field

Abstract: The supramolecular assemblies based on polysaccharides modified by cyclodextrins (CDs) and/or hydrophobic guest molecules have inspired interesting developments in the biomedical, pharmaceutical and cosmetic fields. This review will update the recent progress in the design, synthesis and study of such supramolecular structures. Preliminary studies demonstrated that such systems, based on the physical cross-linking of biopolymers through CD inclusion complexation, have potential as injectable hydrogels for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 70 publications
0
15
0
Order By: Relevance
“…For instance, Rhodes et al 37 showed good linear correlations between amounts of 14 C-phenanthrene mineralised and amounts extracted in control soils (0%) (r 2 ¼ 0.864; slope ¼ 0.89; intercept ¼ 5.74) and 0.1% (r 2 ¼ 0.67; slope ¼ 0.95; intercept ¼ 20.1) AC amended soils. 69,70,72 Prior to extraction, 14 C-phenanthrene molecules would have occupied majority of the micropore sites of the AC, rendering limited or no access for displacement by HPCD extraction. The authors suggested that HPCD extractability was reduced to a greater extent in the presence of AC and microbes had the capability to attach to black carbon surfaces to mineralise 14 C-phenanthrene.…”
Section: Correlation Between Mineralisation and Hpcd Extractabilitymentioning
confidence: 99%
“…For instance, Rhodes et al 37 showed good linear correlations between amounts of 14 C-phenanthrene mineralised and amounts extracted in control soils (0%) (r 2 ¼ 0.864; slope ¼ 0.89; intercept ¼ 5.74) and 0.1% (r 2 ¼ 0.67; slope ¼ 0.95; intercept ¼ 20.1) AC amended soils. 69,70,72 Prior to extraction, 14 C-phenanthrene molecules would have occupied majority of the micropore sites of the AC, rendering limited or no access for displacement by HPCD extraction. The authors suggested that HPCD extractability was reduced to a greater extent in the presence of AC and microbes had the capability to attach to black carbon surfaces to mineralise 14 C-phenanthrene.…”
Section: Correlation Between Mineralisation and Hpcd Extractabilitymentioning
confidence: 99%
“…Recent reviews report host-guest polymer assemblies originated from CD polymers and their biomedical applications. [15][16][17] Zhang and Ma [17] designed different nanocarriers for drug delivery based on a double hydrophilic block copolymer [a poly(ethylene oxide) block and a bCD-containing block]. bCD grafting PEI was proposed to build nanoparticles for drug and gene delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan (CS) is a cationic polysaccharide obtained by the partial deacetylation of chitin, which originates from the shells of crustaceans and has been the second most abundant natural polysaccharide after cellulose . CS has many advantages, such as abundant resources, nontoxicity, biodegradability, biocompatibility, and antibacterial properties; thus, it has been widely used in the fields of agriculture, pharmaceuticals, cosmetics, food industries, environmental protection, and biotechnology .…”
Section: Introductionmentioning
confidence: 99%